Rewards, Workload, and Competence in Relation to Job Satisfaction Among Train Drivers : Reward, Beban Kerja, dan Kompetensi terhadap Kepuasan Kerja Masinis - Fatasya Rizki Fauziah; Mahben Jalil; Deddy Prihadi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Job satisfaction is a crucial factor in human resource management (HRM) that impacts employee productivity, organizational stability, and public transportation safety. Specific Background: In Indonesia’s railway sector, train drivers face high workloads, limited rewards, and insufficient competency development programs, potentially lowering job satisfaction. Knowledge Gap: Previous studies have examined reward systems, workload, and competencies individually or in different industries, leaving limited understanding of their combined effects in the railway sector. Aim: This study aims to analyze the individual and simultaneous effects of rewards, workload, and employee competence on train drivers’ job satisfaction at PT Kereta Api Indonesia (Persero) Daop IV Semarang. Results: Using a quantitative approach with 100 respondents and multiple linear regression analysis, the study found that rewards and competence significantly and positively influence job satisfaction, whereas workload shows no significant effect. Collectively, these factors explain 80.1% of job satisfaction variance. Novelty: This research integrates three key HR factors within the unique operational context of the railway industry, providing empirical evidence not previously explored. Implications: Findings guide transportation management in designing equitable reward systems and competency development programs to enhance employee well-being and operational performance in high-risk public transport environments.Highlight : Rewards and competence have a significant positive effect on job satisfaction. Workload does not have a significant effect on job satisfaction. These three variables together explain 80.1% of the variation in job satisfaction. Keywords : Rewards, Workload, Employee Competence, Job Satisfaction, Train Drivers